A systematic review of coach augmented verbal feedback during practice and competition in team sports - Corbett, R.; Partington, M.; Ryan, L.; Cope, E. (International Journal of Sports Science & Coaching, 2023)
Coaches use of augmented verbal feedback (AVF), often measured through systematic observation, is acknowledged as having a vital role in athlete learning. The purpose of this review was to identify coaches` use of AVF, through systematic observation, in developmental and performance contexts. A literature search was conducted using EBSCO HOST and SCOPUS databases. Studies were reviewed using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Data were extracted from 31 studies which met the inclusion criteria. Analysis revealed three themes: (a) variation in observation tool and feedback types observed; (b) evidence base surrounding feedback types observed; (c) quality of coach feedback. The multiple feedback types measured across the studies suggests there is limited agreement on the types of feedback most important to measure. For the impact of feedback to be better understood, feedback types captured via systematic observation need revising in line with research that has identified the important characteristics of feedback. A greater evidence-informed approach to the observation of feedback may help to develop a greater understanding of the feedback process in learning and performance. Where there were consistencies in feedback type, the quality of AVF delivered by coaches could be questioned.